Cognitive development: no stages please—we're British. - Goswami, Usha (British Journal of Psychology, 2001)
British cognitive developmental psychology is characterized by its interest in philosophical questions, its preference for linking basic research to applied issues in education and cognitive disorders, and its willingness to learn both methodologically and theoretically from work in animal psychology and in physiology more generally. It has also been influenced profoundly by Jean Piaget's cognitive stage theory although in general British work has focused on demonstrating early strengths, rather than early deficits, in infant and child cognition. Following an overview of British work that encompasses past and present interests, issues and challenges for the future are highlighted. While the perspectives of the founding members of the British Psychological Society (BPS), as outlined by Edgell (1947), are still apparent in British research in cognitive developmental psychology today, it is argued that future cognitive work must become even more interdisciplinary and that the symbiotic relationship between research in adult cognition and in cognitive development needs greater recognition. Reprinted by permission of the publisher.